Personal Hygiene Practices and Perceived Health Status of Individuals with Mild Intellectual Disability, in Calabar Metropolis, Cross River State, Nigeria - Ataben, Michael Okaba; Akpan, Victor Bassey; Inah, Roland Afen; Nabiebu, Miebaka; Egbai, Mercy Egbai; Ochai, Donatus Peter; Ntino, Martina Ongbonya; Swem, Terfa; Inah, Emmanuel Mkpe; Obona, Edut Egbe; James, Daniel Daniel; Inyang, Ntongha Yibala; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2026)
Introduction: Globally, individuals with intellectual disabilities face well-documented challenges in maintaining consistent personal hygiene. Evidence from high-, middle-, and low-income settings consistently linked poor hygiene practices to elevated infection risk, social marginalization, and diminished health-related quality of life. Despite this growing body of international evidence, hygiene habits and health perceptions of individuals with Mild Intellectual Disability (MID) in sub-Saharan African contexts, including Nigeria, remain poorly understood and seldom empirically examined. This study investigated the relationship between personal hygiene practices and perceived health status among individuals with MID in Calabar metropolis, Cross River State, Nigeria. Method: Two research questions and one research hypothesis were raised to guide the study. A survey design was employed, and data were collected from a purposive sample of 120 participants aged 10 - 18 enrolled in special education programs. Personal hygiene was measured using a structured Personal Hygiene Checklist completed by the primary teacher or caregiver with the most consistent daily contact with the participant. Where both were available, the individual with the closest routine interaction was selected to minimize variability in observation. Perceived health status was assessed using a Likert-type scale appropriate for students with MID (ranging from poor to very good). Descriptive statistics and ordinal logistic regression were employed to analyze the data at a 0.05 level of significance. Results: Generally poor hygiene practices across key daily care activities, including handwashing, toothbrushing, bathing, nail care, clothing cleanliness, and toilet use, alongside a relatively fair level of perceived health status. Inferential statistics indicated a statistically significant association between personal hygiene behaviors and perceived health status across all hygiene indicators. Conclusion: This research provides evidence of a meaningful association between personal hygiene practices and perceived health status among individuals with MID. These findings indicate that improved hygiene behavior is positively correlated with high perceived health status among persons with MID. Structured hygiene training with visual aids, regular reinforcement, family-school partnership, and periodic monitoring were recommended. The findings can be used to shape school-based support and community-based interventions that are aimed at enhancing preventive health practices among intellectually disabled individuals.